Supporters of Germany’s far-right AfD party are concerned about immigration rather than feeling deprived - Martin Schröder; Moritz Rehm; Anja Röcke (PLoS ONE, 2026)
Is concern about immigration sufficient to account for the increasing success of Germany’s right-wing populist party Alternative für Deutschland (AfD)? Or does socio-economic deprivation also matter? Using German Socio-Economic Panel (SOEP) data from 2014 to 2024, we find that concern about immigration alone accounts for about 75 percent of explicable variation in AfD support and even for 90 percent of explicable variation in voting behaviour. Therefore, variables that measure deprivation explain comparatively little additional variation in AfD support and even less variation in voting for the AfD. Previous research has shown that immigration-concern predicts AfD support. Our results extend this by arguing that the direct relationship between immigration-concern and AfD support is so strong that deprivation variables neither seem to have much additional explanatory power, nor strongly confound the direct relationship between immigration-concern and AfD support. These results undermine the much-cited “losers of modernisation hypothesis”, not only in the sense that socio-economic conditions may be a weaker explanation than cultural ones, but even by questioning whether socio-economic explanations of AfD support have much additional value over cultural explanations at all.